Multiaxial fatigue life prediction of kiln roller under axis line deflection - 沈意平 王送来 李学军 B. S. DHILLON (Applied mathematics and mechanics, 2010)
This paper investigates the multiaxial fatigue life of the roller in rolling contact with wheels with respect to axis line deflection. The multiaxial fatigue criteria proposed by Wang and Brown, together with the ralnflow counting method and Miner- Palmgren＇s rule, are applied to the cumulative damage estimation and life prediction. As the axis line deflection of overlong kilns generally results in asymmetric load distribution on each roller, the load ratio is introduced to describe the deflection for quantitative stress analyses. The stress analyses are performed within the finite element code ANSYS. The tangential friction stress is calculated in terms ：of the condition of the rolling contact area. By taking one roller as an example, the plotted fatigue life versus load ratio curve discovers how the axis line deflection affects the fatigue life. This study is significant to prevent the fatigue failure of the roller and can provide basis to adjust and optimize the axis line of the rotary kiln.